Electrodiffusion Phenomena in Neuroscience and the Nernst–Planck–Poisson Equations - Jasielec Jerzy J. (MDPI, 2022)
This work is aimed to give an electrochemical insight into the ionic transport phenomena in the cellular environment of organized brain tissue. The Nernst–Planck–Poisson (NPP) model is presented, and its applications in the description of electrodiffusion phenomena relevant in nanoscale neurophysiology are reviewed. These phenomena include: the signal propagation in neurons, the liquid junction potential in extracellular space, electrochemical transport in ion channels, the electrical potential distortions invisible to patch-clamp technique, and calcium transport through mitochondrial membrane. The limitations, as well as the extensions of the NPP model that allow us to overcome these limitations, are also discussed. View Full-Text
Keywords: electrodiffusion; Nernst–Planck–Poisson; neuroscience; neurons; liquid junction potential; ionic channels; patch-clamp